2021
DOI: 10.21203/rs.3.rs-696505/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Reported Symptom Study of COVID-19 Chemosensory Dysfunction in Malaysia

Abstract: Alterations in the three chemosensory modalities – smell, taste, and chemesthesis – have been implicated in Coronavirus Disease 2019 (COVID-19), yet emerging data suggest a wide geographic and ethnic variation in the prevalence of these symptoms. Studies on chemosensory disorders in COVID-19 have predominantly focused on Caucasian populations whereas Asians remain understudied. We conducted a nationwide, multicentre cross-sectional study using an online questionnaire on a cohort of RT-PCR-confirmed adult COVID… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…When anosmia prevalence was determined early during the pandemic in Malaysia (in April 2020), while the D614 virus was still dominant, with only a minor contribution of the G614 virus, the anosmia prevalence was 21.4% . Just 3–5 months later, when the G614 virus dominated, , the anosmia prevalence had increased to 36.6%, consistent with our hypothesis.…”
Section: Supporting Evidence For a Role Of G614 In Anosmia Prevalencesupporting
confidence: 86%
“…When anosmia prevalence was determined early during the pandemic in Malaysia (in April 2020), while the D614 virus was still dominant, with only a minor contribution of the G614 virus, the anosmia prevalence was 21.4% . Just 3–5 months later, when the G614 virus dominated, , the anosmia prevalence had increased to 36.6%, consistent with our hypothesis.…”
Section: Supporting Evidence For a Role Of G614 In Anosmia Prevalencesupporting
confidence: 86%
“…The questionnaire was adapted from an existing online questionnaires developed by the Global Consortium for Chemosensory Research (GCCR) (Parma et al 2020). The GCCR core questionnaire that implemented in 10 languages as of April 18, 2020 was used or adapted in many other research (Lee et al 2022;Cecchetto et al 2021;Albayay et al 2022). Data collected included the demographic, COVID-19-related characteristics and chemosensory situation before and during infection.…”
Section: Data Collectionmentioning
confidence: 99%
“…Information from the World Health Organization (WHO) shows that the number of confirmed COVID-19 cases was 756,411,740 by 16 February, 2023 (https://covid19.who.int). Some reports has shown that chemosensory disorders are important symptoms of COVID-19 infection (Al-Rawi et al 2022;Lee et al 2022;Parma et al 2020). Studies from the United States, Europe, Malaysia and Singapore showed that 12%-88% of COVID-19 infected patients have olfactory and taste disorders (Lechien et al 2020;Menni et al 2020;Lee et al 2022;Tham et al 2021).…”
Section: Introductionmentioning
confidence: 99%